Inflammatory and cytotoxic effects of bifenthrin in primary microglia and organotypic hippocampal slice cultures - Brahim Gargouri; Nizar M. Yousif; Michèle Bouchard; Hamadi Fetoui; Bernd L. Fiebich (Journal of Neuroinflammation, 2018)
Abstract Background Pyrethroids, such as bifenthrin (BF), are among the most widely used class of insecticides that pose serious risks to human and wildlife health. Pyrethroids are proposed to affect astrocytic functions and to cause neuron injury in the central nervous system (CNS). Microglia are key cells involved in innate immune responses in the CNS, and microglia activation has been linked to inflammation and neurotoxicity. However, little information is known about the effects of BF-induced toxicity in primary microglial cells as well as in organotypic hippocampal slice cultures (OHSCs). Methods Oxidative stress and inflammatory responses induced by BF were evaluated in primary microglial cells and OHSCs incubated with different concentrations of BF (1–20 μM) for 4 and 24 h. mRNA and protein synthesis of cyclooxygenase-2 (COX-2), tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), nuclear erythroid-2 like factor-2 (Nrf-2), and microsomal prostaglandin synthase-1 (mPGES-1) was also studied by qPCR and Western blot. Cell viability was analyzed by MTT-tetrazolio (MTT) and lactate dehydrogenase (LDH) assays. Neurotoxicity in OHSCs was analyzed by propidium iodide (PI) staining and confocal microscopy. Results Exposure of microglial cells to BF for 24 h resulted in a dose-dependent reduction in the number of viable cells. At sub-cytotoxic concentrations, BF increased reactive oxygen species (ROS), TNF-alpha synthesis, and prostaglandin E2 (PGE2) production, at both 4- and 24-h time points, respectively. Furthermore, BF incubation decreased superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities and increased lipid peroxidation, protein oxidation, and H2O2 formation. In addition, BF significantly induced protein synthesis and mRNA expression of oxidative and inflammatory mediators after 4 and 24 h, including Nrf-2, COX-2, mPGES-1, and nuclear factor kappaB (NF-kappaB). A 24-h exposure of OHSCs to BF also increased neuronal death compared to untreated controls. Furthermore, depletion of microglia from OHSCs potently enhanced neuronal death induced by BF. Conclusions Overall, BF exhibited cytotoxic effects in primary microglial cells, accompanied by the induction of various inflammatory and oxidative stress markers including the Nrf-2/COX-2/mPGES-1/NF-kappaB pathways. Moreover, the study provided evidence that BF induced neuronal death in OHSCs and suggests that microglia exert a protective function against BF toxicity.